38. A PILOT STUDY TO EVALUATE ANTIBACTERIAL POTENTIALS OF ADVANCED PLATELET-RICH FIBRIN PLUS AGAINST TWO DIFFERENT STRAINS OF STAPHYLOCOCCUS AUREUS (Vietnam Journal of Community Medicine, 2026)
platelet-rich fibrin plus (A-PRF+) against two strains of Staphylococcus aureus.Method: A-PRF+ samples were collected from three volunteers who met the inclusion criteria. The bacterial strains used were methicillin-sensitive Staphylococcus aureus (MSSA, ATCC 6538) and methicillin-resistant Staphylococcus aureus (MRSA, ATCC 33591). Both strains were reactivated following the manufacturer's instructions and prepared at a concentration equivalent to 0.5 McFarland standard for the experiments. Venous blood from each volunteer was collected by a trained nurse and transferred into A-PRF+ and S-PRF tubes. The tubes were centrifuged at 1300 rpm for 8 minutes. Antibacterial activity was preliminarily assessed using three assays: agar diffusion, minimum inhibitory concentration (MIC), and biofilm formation inhibition.Results: A clear inhibition zone was observed around A-PRF+ clots on agar plates inoculated with MSSA and MRSA, with mean diameters of 0.59 mm and 0.73 mm, respectively. In the MIC assay, A-PRF+ from all three volunteers inhibited both MSSA and MRSA at a 1:4 dilution. In the biofilm inhibition test using a 96-well microplate, the percentage of surface area covered by biofilm after 24-hour incubation in the presence of A-PRF+ was 57.20% for MSSA and 63.54% for MRSA.Conclusion: Preliminary findings suggest that A-PRF+ exhibits antibacterial potential against both methicillin-sensitive and methicillin-resistant strains of Staphylococcus aureus. However, studies with larger sample sizes are necessary to confirm and further characterize the antibacterial efficacy of A-PRF+ against S. aureus.
Keywords: advanced platelet-rich fibrin plus, antibacterial capacity, Staphylococcus aureus, pilot study.